Short term efficacy of nebulized beclomethasone in mild-to-moderate wheezing episodes in pre-school children - Cutrera Renato; Baraldi Eugenio; Boner Attilio L; Nicolini Gabriele; Papi Alberto; Fabbri Leonardo M; Rossi Giovanni A (BMC, 2011)
Abstract Background Few data are available on the usefulness of short term treatment with low-medium dose of inhaled corticosteroids (ICS) in pre-school children with wheezing exacerbations. Methods To compare the efficacy of one week treatment with 400 μg b.i.d. nebulized beclomethasone dipropionate (BDP), plus nebulized 2500 μg prn salbutamol (BDP group), versus nebulized b.i.d. placebo, plus nebulized prn 2500 μg salbutamol (placebo group), a post-hoc analysis was performed on data obtained in 166 pre-school children with multiple-trigger wheezing, recruited during an acute wheezing episode. Results The percentage of symptom-free days (SFDs) was significantly higher in the BDP group (54.7%) than in the placebo group (40.5%; p = 0.012), with a 35% relative difference. Day-by-day analysis showed that the percentage of SFDs was already higher in the BDP group after 2 days (7.4%), the difference reaching statistical significance at day 6 (12.3%; p = 0.035). Cough score was also reduced in the BDP group (0.11) as compared with the placebo group (0.39; p = 0.048), the difference reaching statistical significance after 5 days of treatment (0.18 and 0.47 respectively; p = 0.047). The mean number of nebulizations per day of prn salbutamol was lower in the BDP group as compared to the placebo group (0.26 and 0.34, respectively), but the difference was not significant (p = 0.366). There were no differences in positive effects of BDP treatment between children with and without risk factors for asthma. Conclusions A 1-week treatment with nebulized BDP and prn salbutamol is effective in increasing SFDs and improving cough in children with wheezing, providing a clinical rationale for the short term use of ICS in episodic wheeze exacerbations in pre-school children. Trial Registration ClinicalTrials.gov (NCT00497523)